What Is Going on Inside the Arrows? Discovering the Hidden Springs in Causal Models. Issue 4 (October 2015) - Murray-Watters, Alexander; Glymour, Clark
Abstract : Using Gebharter's representation, we consider aspects of the problem of discovering the structure of unmeasured submechanisms when the variables in those submechanisms have not been measured. Exploiting an early insight of Sober's, we provide a correct algorithm for identifying latent, endogenous structure—submechanisms—for a restricted class of structures. The algorithm can be merged with other methods for discovering causal relations among unmeasured variables, and feedback relations between measured variables and unobserved causes can sometimes be learned.